ANALYSIS OF JUDGES' CONSIDERATIONS IN CRIMINAL DECISIONS ON RAPE OF MINORS - Kodai, Dince Aisa; Nurmala, Leni Dwi (Universitas Islam Negeri Ar-Raniry, 2024)
Crime can happen to anyone and anywhere. One of the crimes that can cause victims experienced by adults and even children is a crime against sex. However, it is even more concerning when sexual crimes, for example rape, occur in minors. This can cause psychological and physical trauma for the future of the child. In Indonesia, children are vulnerable to becoming victims of sexual crimes. The method used is empirical legal research, namely research that examines law in reality or reality in society with a judicial case study approach, namely where there is a conflict in this approach, the court will intervene to provide assistance in the form of decisions related to problem solving. The legal case study approach is the analysis of the decision Number 58/Pid.Sus/2021/PN Gto. Based on the results of the discussion, the perpetrators of rape of minors can be charged using Article 81 paragraph (1) of the Law of the Republic of Indonesia Number 35 of 2014 concerning Child Protection.